Faktor Yang Mempengaruhi Kejadian Ketuban Pecah Dini Pada Kehamilan Trimester III di Puskesmas Silo Kabupaten Jember. - Lestari, Dwi Anggun (MEDICAL JURNAL OF AL-QODIRI, 2020)
Premature rupture of membranes is rupture of membranes in pregnant women before any sign of labor. The direct cause of maternal death in Indonesia is 27% due to premature rupture of membranes which can ultimately lead to complications in puerperium. Based on the 2017 Riskesdas data, the Maternal Mortality Rate was 348 per 100,000 live births in 2015. In 2018 Jember district has a higher maternal mortality rate than the province. In 2018 at the Silo Health Center in Jember District, there were 239 cases of premature rupture of membranes in pregnant women. The purpose of this study was to study and explain the description of the incidence of premature rupture of membranes in pregnant women. The research design used is case control through a retrospective approach. The population in this study were 275 third trimester pregnant women with 153 mothers experiencing premature rupture of membranes and 122 who did not experience premature rupture of membranes. The sample size in this study was 122 cases and 122 controls. The control sample was taken by simple random sampling. Data collection was performed using medical records. The analysis of this study used univariate, bivariate using Chi Square (X²) and multivariate with Simple Logistic Regression test. In this study, the variables that influence the occurrence of premature rupture of membranes are age, occupation, parity, multiple pregnancy, fetal abnormalities, birth spacing and history of KPD with p value <0.05. The most dominant variable on the occurrence of premature rupture of membranes is the history of KPD with OR = 40.137: 95% CI and p value 0.000 so that different proportions of cases and controls are significant in the sense that there is a significant influence between the history of KPD on the incidence of premature rupture of membranes. So it is expected for third trimester pregnant women to be more diligent in doing ANC (Antenatal Care) in the next pregnancy.